Long-QT founder variant T309I-Kv7.1 with dominant negative pattern may predispose delayed afterdepolarizations under β-adrenergic stimulation - Synková, Iva; Bébarová, Markéta; Andršová, Irena; Chmelikova, Larisa; Švecová, Olga; Hošek, Jan; Pásek, Michal; Vít, Pavel; Valášková, Iveta; Gaillyová, Renata; Navrátil, Rostislav; Novotný, Tomáš (Scientific reports, 2021)
The variant c.926C > T (p.T309I) in KCNQ1 gene was identified in 10 putatively unrelated Czech families with long QT syndrome (LQTS). Mutation carriers (24 heterozygous individuals) were more symptomatic compared to their non-affected relatives (17 individuals). The carriers showed a mild LQTS phenotype including a longer QTc interval at rest (466 ± 24 ms vs. 418 ± 20 ms) and after exercise (508 ± 32 ms vs. 417 ± 24 ms), 4 syncopes and 2 aborted cardiac arrests. The same haplotype associated with the c.926C > T variant was identified in all probands. Using the whole cell patch clamp technique and confocal microscopy, a complete loss of channel function was revealed in the homozygous setting, caused by an impaired channel trafficking. Dominant negativity with preserved reactivity to β-adrenergic stimulation was apparent in the heterozygous setting. In simulations on a human ventricular cell model, the dysfunction resulted in delayed afterdepolarizations (DADs) and premature action potentials under β-adrenergic stimulation that could be prevented by a slight inhibition of calcium current. We conclude that the KCNQ1 variant c.926C > T is the first identified LQTS-related founder mutation in Central Europe. The dominant negative channel dysfunction may lead to DADs under β-adrenergic stimulation. Inhibition of calcium current could be possible therapeutic strategy in LQTS1 patients refractory to β-blocker therapy.
Keywords: genetické asociační studie; detekce genetických nosičů; genetická predispozice k nemoci; homozygot; syndrom dlouhého QT; Europe; Adrenergic beta-Antagonists; Adult; rodokmen; Male; lidé; Genotype; Haplotypes; Humans; heterozygot; Homozygote; Mutation; Evropa; KCNQ1 Potassium Channel; haplotypy; Heterozygote; Long QT Syndrome; Phenotype; mužské pohlaví; fenotyp; Genetic Predisposition to Disease; Genetic Carrier Screening; dospělí; Genetic Association Studies; draslíkový kanál KCNQ1; ženské pohlaví; genotyp; mutace; Female; beta blokátory; Pedigree